TRANSFER TEKNOLOGI BIOFLOK PADA BUDIDAYA IKAN NILA SEBAGAI UPAYA PEMBERDAYAAN EKONOMI TERHADAP EKS PECANDU NARKOBA DI KOTA BANDA ACEH - Dedi Fazriansyah Putra; Irwan Irwan; Monalisa Monalisa (Universitas Mataram, 2022)
Aceh province ranks 12th nationally in drug cases. The problem faced by former drug addicts is the negative stigma attached to them, which makes it difficult for them to be accepted both at work and at work. The purpose of the community partnership program (PKM) through technology transfer for tilapia biofloc cultivation is as an effort to empower the economy of former drug addicts who have experienced a negative stigma so that it is difficult to be accepted in the community or as employees in the company. One of the alternative life skills offered is that former drug users can independently carry out fish farming businesses to make a living. This biofloc tilapia cultivation technology transfer activity has been carried out from March to October 2021 in partnership with the Imam Ahmad bin Idris Aceh Foundation which has experience in carrying out mental and life skill development activities in Lambugob Village, Syiah Kuala District, Banda Aceh. The parties involved in this activity are young former drug addicts who were fostered by the Imam Ahmad bin Idris Aceh Foundation. Partners have been introduced to a comprehensive biofloc system cultivation technology including simple biofloc pond design, fish rearing techniques, feeding techniques, water quality care, harvesting to business and marketing analysis. The stages of this PKM service activity consist of 3 (three) stages, namely: Socialization and preparation, implementation of tilapia biofloc technology applications and evaluation through focus group discussions with partners, government and relevant stakeholders. It is hoped that this technology dissemination activity can play a role in supporting the program to accelerate the downstream process of technological products resulting from research by academics that can be utilized by the community towards a prosperous Indonesia.